2014
DOI: 10.4161/hv.28618
|View full text |Cite
|
Sign up to set email alerts
|

A dose-ranging study in older adults to compare the safety and immunogenicity profiles of MF59®-adjuvanted and non-adjuvanted seasonal influenza vaccines following intradermal and intramuscular administration

Abstract: Strategies to optimize responses to seasonal influenza vaccination in older adults include the use of adjuvants, higher antigen doses, and intradermal delivery. In this study adults aged >= 65 years (n = 450) received a single dose of 1 of 2 non-adjuvanted trivalent influenza vaccine (TIV) formulations administered intradermally (ID), both containing 6 mu g of A/H1N1 and B, differing in A/H3N2 content (6 mu g or 12 mu g), or a single dose of 1 of 8 TIV formulations administered intramuscularly (IM) all contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…60,61,68 A study in the elderly compared fractional-dose ID delivery to the full IM dose of the unadjuvanted influenza vaccine (Fluvirin TM , Novartis), as well as to MF59-adjuvanted formulations with various antigen and adjuvant doses. 108 This study showed that the unadjuvanted ID approach yielded significantly higher immunogenicity at 6 mg HA/strain than unadjuvanted IM formulations at 15 mg or 30 mg HA/strain, in at least the A/ H1N1 strain, with non-inferior GMTs in the other strains. One study arm (12 mg HA/strain ID) was also higher with the A/ H3N2 strain compared to the unadjuvanted IM formulations.…”
Section: The Past: Clinical Results With the Original Micronjet Devicementioning
confidence: 91%
“…60,61,68 A study in the elderly compared fractional-dose ID delivery to the full IM dose of the unadjuvanted influenza vaccine (Fluvirin TM , Novartis), as well as to MF59-adjuvanted formulations with various antigen and adjuvant doses. 108 This study showed that the unadjuvanted ID approach yielded significantly higher immunogenicity at 6 mg HA/strain than unadjuvanted IM formulations at 15 mg or 30 mg HA/strain, in at least the A/ H1N1 strain, with non-inferior GMTs in the other strains. One study arm (12 mg HA/strain ID) was also higher with the A/ H3N2 strain compared to the unadjuvanted IM formulations.…”
Section: The Past: Clinical Results With the Original Micronjet Devicementioning
confidence: 91%
“…The MF59 oil-in-water adjuvant (Adj) emulsion enhances influenza responses in the elderly and is licensed for immunization of individuals aged 65 years and older (9)(10)(11). In infants, a first trial evaluating MF59-adjuvanted versus nonadjuvanted monovalent A/H1N1 influenza vaccines between 6 and 36 months of age showed that MF59-adjuvanted formulations generated higher response rates with persistent seroprotection (12).…”
mentioning
confidence: 99%
“…In order to promote a regulatory response to the PIC19-A3 autoantigen we employed the CE-marked MJ600 device to target skin DCs whilst minimising the trauma of intradermal delivery and any ensuing cutaneous inflammation (Mutyambizi et al, 2009). The device has three hollow silicon MNs of 600μm length and has been used extensively in clinical studies to deliver a range of macromolecular formulations including insulin (Kochba et al, 2016), varicella zoster (Beals et al, 2016), polio (Anand et al, 2015;Troy et al, 2015) and seasonal and pandemic influenza vaccines (Della Cioppa et al, 2014;Hung et al, 2012a;Hung et al, 2012b;Levin et al, 2014;Levin et al, 2016;Van Damme et al, 2009). However, whilst there are a number of publications showing successful therapeutic readouts upon use of hollow MNs, there is a paucity of information related to the behaviour of injected materials in the local environment and how formulation or physicochemical drug properties influence distribution and retention in situ (Mansoor et al, 2015).…”
Section: Resultsmentioning
confidence: 99%